THE REPRESENTATION OF EGYPTIAN AND SYRIAN GOVERNMENTS IN BBC AND CNN TEXTS REGARDING THE CIVIL WARS IN EGYPT AND SYRIA - Ma'ruf, Khaerul (2014)
This research probes the representation of social actors in two prominent Western mass media and examines ideologies behind such representation by using social actor classification (van Leeuwen, 2008) and Transitivity (Halliday and Matthiessen, 2004). The Egyptian and Syrian governments are the focuses of this research. The data of this research were taken from two Western mass media, namely BBC and CNN. The research is descriptive qualitative in nature. The data include the online news articles published in official sites of BBC and CNN. The analysis examines how social actors are excluded and included in the texts. The findings showed that BBC and CNN mostly represent the Egyptian and Syrian governments negatively. It was discovered from the excessive use of predicates with negative semantic load attached to the Egyptian and Syrian governments. Such excessive use of predicates implicates that BBC and CNN were likely to expose the bad sides of the Egyptian and Syrian governments to the world citizen. This practice appears to reflect how the two media view the two national governments. Furthermore, the findings also showed that (im)partiality, democracy, and consumerism were the ideologies that appeared in the texts. Keywords: Representation, the mass media, Egyptian and Syrian Government